2006
DOI: 10.1016/j.ultrasmedbio.2005.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Vascular lesions and s-thrombomodulin concentrations from auricular arteries of rabbits infused with microbubble contrast agent and exposed to pulsed ultrasound

Abstract: Arterial injury resulting from the interaction of contrast agent (CA) with ultrasound (US) was studied in rabbit auricular arteries and assessed by histopathologic evaluation and s-thrombomodulin concentrations. Three sites on each artery were exposed (2.8 MHz, 5-min exposure duration, 10-Hz pulse repetition frequency, 1.4-μs pulse duration) using one of three in situ peak rarefactional pressures (0.85, 3.9 or 9.5 MPa). Saline, saline/CA, and saline/US infusion groups (n = 28) did not have histopathologic dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…Recent studies have investigated the potential therapeutic benefits of acoustically stimulated microbubbles in biological systems. These studies have reported increased vascular permeability, decreased vascular integrity, the creation of vascular-based lesions, hemorrhaging, and endothelial cell death depending on ultrasound pressures and frequencies used [ 4 , 6 9 ]. In vivo studies have demonstrated the use of acoustically stimulated microbubbles to re-open acutely thrombosed vessels using either platelet-targeted or lipid-encapsulated microbubbles [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the potential therapeutic benefits of acoustically stimulated microbubbles in biological systems. These studies have reported increased vascular permeability, decreased vascular integrity, the creation of vascular-based lesions, hemorrhaging, and endothelial cell death depending on ultrasound pressures and frequencies used [ 4 , 6 9 ]. In vivo studies have demonstrated the use of acoustically stimulated microbubbles to re-open acutely thrombosed vessels using either platelet-targeted or lipid-encapsulated microbubbles [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of pFUS alone or the interaction of pFUS with some contrast agents (CA) may lead to violent oscillation and/or collapse of CA and, in vivo, the hypothetical formation of shear stress forces or thermal changes (heat or microjets), denaturation and coagulation of cell membrane and cytoplasmic proteins and cell necrosis. 28 In this work, we have used an acoustic power of 25 W and a 10% duty cycle for the pFUS sonication, which kept the temperature elevation below 5 • C in our phantom measurements and in targeted tumor tissues in mice as measured by MR thermometry (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro and in vivo bioeffects of UCAs have been noted, including hemolysis, 3 capillary rupture, 4 endothelial cell damage, 5 and elevations in troponin T, a biomarker of cardiac damage 6 . Previous studies in our laboratory have demonstrated UCA‐induced arterial endothelial and vascular smooth muscle injury 7 and cardiac arrhythmias 8 . These results suggest that the interactions of US with UCAs in the cardiovascular system may have important consequences, especially if exposure to contrast US hastens the onset or increases the severity of atherosclerosis in patients at risk.…”
mentioning
confidence: 96%